Effectiveness of pulmonary interventions on clinical outcomes among patients with chronic obstructive pulmonary disease: a randomized controlled trial - Rathod, Yogendra; Z Patel, Dr. Mahendra; HN, Dr. Ravindra; Rahane, Dr. Swapnil (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disorder characterized by persistent airflow limitation, dyspnea, impaired gas exchange, and reduced exercise tolerance. Pulmonary interventions are recognized as effective non-pharmacological strategies for improving respiratory function and clinical outcomes among COPD patients. However, evidence regarding their effectiveness in local healthcare settings remains limited. Objective: To evaluate the effectiveness of pulmonary interventions on clinical outcomes among patients with Chronic Obstructive Pulmonary Disease in selected hospitals of Vadodara City. Methods: A quantitative research approach with a randomized controlled trailed, pre-test post-test control group design was adopted. The study was conducted among 120 COPD patients selected from hospitals in Vadodara City. Participants were randomly assigned to an experimental group (n=60) and a control group (n=60). The experimental group received a structured pulmonary intervention package comprising diaphragmatic breathing, pursed-lip breathing, chest expansion exercises, and supervised walking exercises for six weeks, while the control group received routine care. Clinical outcomes assessed included dyspnea severity using the Modified Medical Research Council (mMRC) Scale, oxygen saturation (SpO₂), respiratory rate, and six-minute walk distance (6MWD). Data were analyzed using descriptive and inferential statistics, including paired and independent t-tests. Results: Baseline clinical outcomes were comparable between the experimental and control groups. Following six weeks of intervention, the experimental group demonstrated significant improvement in all measured outcomes. Mean dyspnea score decreased from 3.20 ± 0.72 to 1.65 ± 0.63, compared to 3.15 ± 0.68 to 2.95 ± 0.65 in the control group (t=10.82, p<0.001). Mean oxygen saturation increased from 92.3 ± 1.9% to 95.8 ± 1.4% in the experimental group, whereas only a marginal improvement was observed in the control group (t=8.96, p<0.001). Respiratory rate decreased significantly from 24.8 ± 2.6 to 19.8 ± 2.1 breaths per minute in the experimental group compared with the control group (t=8.11, p<0.001). Similarly, six-minute walk distance improved from 278 ± 49 meters to 382 ± 56 meters in the experimental group, while minimal improvement was observed in the control group (t=8.74, p<0.001). Conclusion: The findings indicate that pulmonary interventions were effective in improving clinical outcomes among COPD patients. Significant reductions in dyspnea and respiratory rate, along with improvements in oxygen saturation and exercise capacity, were observed among participants receiving the intervention. Integration of structured pulmonary interventions into routine COPD management may enhance patient outcomes and functional performance.